MEASURING UNIVERSAL HEALTH COVERAGE BASED ON AN INDEX OF EFFECTIVE COVERAGE OF HEALTH SERVICES IN 204 COUNTRIES AND TERRITORIES, 1990-2019: A SYSTEMATIC ANALYSIS FOR THE GLOBAL BURDEN OF DISEASE STUDY 2019 - Lozano, R.; Fullman, N.; Mumford, J. E.; Knight, M.; Barthelemy, C. M.; Abbafati, C.; Abbastabar, H.; Abd-Allah, F.; Abdollahi, M.; Abedi, A.; Abolhassani, H.; Abosetugn, A. E.; et al. (Elsevier, 2020)
Achieving universal health coverage (UHC) involves all people receiving the health services they need, of high quality, without experiencing financial hardship. Making progress towards UHC is a policy priority for both countries and global institutions, as highlighted by the agenda of the UN Sustainable Development Goals (SDGs) and WHO’s Thirteenth General Programme of Work (GPW13). Measuring effective coverage at the health-system level is important for understanding whether health services are aligned with countries’ health profiles and are of sufficient quality to produce health gains for populations of all ages.
Keywords: universal health coverage; UHC; Type of access: Open Access; Research Subject Categories::MEDICINE; Global Burden of Diseases; GBD